2015
DOI: 10.1515/hukin-2015-0128
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Strength Profile of Elite Female Handball Players

Abstract: Systematic assessment of muscle strength of the lower extremities throughout the annual training cycle in athletes is crucial from a performance perspective for the optimization of the training process, as well as a health perspective with regard to injury prevention. The main aim of the present study was to determine isokinetic muscle strength of the knee flexors and extensors in female handball players at the beginning of a preparatory period and to assess whether there were any differences between players o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 26 publications
2
27
1
8
Order By: Relevance
“…Our volunteers demonstrated lower strength values of knee flexor and extensor muscles than previous data of elite soccer players . Athletes of both sexes involved with FMHI, however, demonstrated higher shoulder strength values than those demonstrated by women wrestlers and by elite female athletes or male handball players .…”
Section: Discussioncontrasting
confidence: 68%
“…Our volunteers demonstrated lower strength values of knee flexor and extensor muscles than previous data of elite soccer players . Athletes of both sexes involved with FMHI, however, demonstrated higher shoulder strength values than those demonstrated by women wrestlers and by elite female athletes or male handball players .…”
Section: Discussioncontrasting
confidence: 68%
“…Arm asymmetry was also observed in professional tennis players, with approximately 20 % more bone mineral content and muscle mass in the dominant arm (Calbet et al, 1998). Xaverova et al (2015), found that a bilateral force deficit is more frequent in adult female handball players compared to junior players, which could be due to long-term unilateral orientation of handball-specific skills. Strength asymmetry across the body has been shown to be linked to increased prevalence of injury (McCall et al, 2014) and impaired performance in athletes (Young et al, 2002).…”
Section: Introductionmentioning
confidence: 89%
“…Otro factor fuertemente involucrado con la incidencia de la lesión del LCA, es el equilibrio muscular entre el cuádriceps e isquiotibiales, que algunos autores consideran como un factor intrínseco, por ser una cualidad individual de la característica de las fibras y otros extrínsecos por tener una característica específica para el deporte practicado, posición y tiempo de entrenamiento (Xaverova et al, 2015). Los valores de referencia poblacional adoptados para evaluar la condición de fuerza de la paciente se basaron en el estudio de Danneskiold-Samsoe et al (2009), que determina los valores de torque concéntricos en 132N para extensores y 74.4N para flexores y valores cerca del 30% mayores de torque excéntrico (Xaverova et al, 2015).…”
Section: Discussionunclassified
“…Los valores de referencia poblacional adoptados para evaluar la condición de fuerza de la paciente se basaron en el estudio de Danneskiold-Samsoe et al (2009), que determina los valores de torque concéntricos en 132N para extensores y 74.4N para flexores y valores cerca del 30% mayores de torque excéntrico (Xaverova et al, 2015). En relación con los valores poblacionales y los de la paciente, se percibe respecto a los valores concéntricos, que presentaba, con excepción de la evaluación del 2008, valores inferiores a los predichos para su franja etaria, de acuerdo a además de los largos periodos de rehabilitación y las expectativas para un nuevo retorno frustrado al deporte.…”
Section: Discussionunclassified